2018
DOI: 10.1016/j.jvs.2018.05.253
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 decreases abdominal aortic aneurysm formation by inhibiting NETosis in a mouse model

Abstract: Objectives: Resolvins have been shown to attenuate inflammation, while NETosis, the process of neutrophils releasing neutrophil extracellular traps (NETs), produces increased inflammation. It is hypothesized that treatment of animals with resolvin D1 (RvD1) would reduce abdominal aortic aneurysm (AAA) formation by inhibiting NETosis. Methods: Wild-type (WT) 8–12-week old C57BL/6 male mice (n=47) and apolipoproteinE deficient (ApoE-/) mice (n=20) were used in two models to demonstrate the effects of RvD1 on A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 39 publications
5
53
0
Order By: Relevance
“…However, Capo et al showed in 2015 that neutrophils extracted from the blood of sportsmen whose diet had been supplemented with DHA and EPA secreted lower amounts of IL-6 upon PMA stimulation [79]. A single report in 2018 investigated the effects of Resolvin D1 on NET production, i.e., in an abdominal aortic aneurysm mouse model Resolvin D1 decreased NET formation [80]. We were not able to find a single report investigating the effect of omega-3 fatty acids on neutrophil degranulation.…”
Section: Effects Of Omega-3 Fatty Acids On Neutrophil Functionmentioning
confidence: 99%
“…However, Capo et al showed in 2015 that neutrophils extracted from the blood of sportsmen whose diet had been supplemented with DHA and EPA secreted lower amounts of IL-6 upon PMA stimulation [79]. A single report in 2018 investigated the effects of Resolvin D1 on NET production, i.e., in an abdominal aortic aneurysm mouse model Resolvin D1 decreased NET formation [80]. We were not able to find a single report investigating the effect of omega-3 fatty acids on neutrophil degranulation.…”
Section: Effects Of Omega-3 Fatty Acids On Neutrophil Functionmentioning
confidence: 99%
“…Changes in these AAA-related factors are consistent with those observed in human AAA [ 27 , 42 , 43 ]. Neutrophil elastase, which is released by activated neutrophils, plays an important role in the development of AAA [ 64 , 65 ]. It reportedly regulates the formation of neutrophil extracellular traps (NETs) [ 66 ], which play a critical role in the neutrophil-mediated development of AAA [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the inflammatory cells, neutrophils are among the most abundant cell types and the first cell population recruited to the site of injured aortic wall. 7,8 After infiltration and activation, neutrophils release pro-inflammatory molecules such as interleukin-6 (IL6), neutrophil-associated proteases and extracellular traps (NETs), matrix metalloproteinases (MMP) such as MMP-9, cysteinyl cathepsins, and myeloperoxidase to induce aortic wall inflammation, vascular cell apoptosis, and matrix degradation, [9][10][11][12][13] leading to aortic rupture. Depletion of circulating neutrophils by using anti-neutrophil antibody or targeting neutrophil recruitment required chemokines or adhesion molecules inhibited AAA development in aortic elastase perfusion or peri-aortic calcium phosphate injury-induced mouse AAA models, 7,8,14,15 supporting an important role of neutrophils in AAA formation.…”
Section: Introductionmentioning
confidence: 99%